A model for heat transfer in cohesive cracks. (February 2017) - Jaśkowiec, J.
Abstract: This paper is concerned with modeling of heat flow through cracks in three-dimensional thermo-mechanical problems. Various aspects connected with heat flow through crack are analyzed in the model. The analysis leads to the model that takes into account the following elements: crack opening, crack sliding, conductivity through bridging elements, conductivity through air between crack faces and heat radiation between crack faces. The model for the crack heat flow is combined with cohesive crack model. The global formulation is evaluated for the problem which is nonlinear due to nonlinear relations in the applied crack model, so the linearization is proposed. Both of the fields, namely the displacement and the temperature field, are discontinuous along the crack surface. Therefore, the solution procedure is based on XFEM approach that is applied for both mechanical and thermal parts. In consequence, the coupled linearized system of equations is evaluated.